Open access: Māori perspectives on publishing - Lilley, Spencer (Information Research an international electronic journal, 2025)
Introduction. This short paper presents the results of a project that looked at Māori researchers’ attitudes to open access publishing. It presents an overview of their engagement with green and gold publishing options, including barriers and challenges they encountered when considering open access publishing and the role that Māori liaison librarians have in encouraging Māori academics to utilize the range of open access resource opportunities available. Method. In this study, six Māori researchers and four Māori liaison librarians were interviewed using a kaupapa Māori methodological approach. Results. The results were analysed using a tikanga Māori focused lens Conclusions. Although the Māori researchers in this study are aware of open access publishing, they were unsure of how to distinguish between the different models on offer and would benefit from regular engagement and advice from Māori liaison librarians.